Digitalisasi Proses Pengajuan Pinjaman Berbasis Web Menggunakan Metode Agile pada PT. Mekar Harum Dinamika - Ilman Fahmi; Muhammad Lukmanul Arifin; Muhammad Lukmanul Irfan; Andriansah Andriansah (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
PT. Mekar Harum Dinamika (PT. MHD) is a company that provides fronting services for loan applications submitted by Indonesian Civil Servants, namely the State Civil Apparatus (ASN) or Civil Servants (PNS). Customer data management and loan application processing are still carried out using Microsoft Excel, while document exchange is conducted through WhatsApp. These practices result in a high risk of recording errors, data duplication, difficulties in retrieving information, and delays in report generation, which reduce the overall effectiveness of business processes. This study aims to implement a web-based loan application management information system to support customer data management, loan application processing, incentive submission, document verification, application status monitoring, and integrated report generation. The system was developed using the Agile methodology, enabling iterative development and continuous adaptation to user requirements. The application was built using the Laravel framework and MySQL database to ensure structured and secure data management. The results of this study indicate that the developed system improves the effectiveness and efficiency of loan application management, reduces data processing errors, accelerates information retrieval and report generation, and enables administrators and marketing staff to monitor the entire loan application process in real time. Consequently, the system supports faster and more accurate decision-making while enhancing the overall quality of loan management services.